2012
DOI: 10.4103/2230-8210.95684
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in newly diagnosed breast cancer patients

Abstract: Aim:The aim was to determine serum vitamin D levels in breast cancer patients and to assess its risk association with grade and stage of the tumor.Materials and Methods:Ninety breast cancer patients and equal number of age-matched healthy females were recruited into the study by consecutive sampling over a period of 6 months for this case control study. Serum 25(OH)2D levels and CT bone mineral density was done.Results:The mean age was 46±1.5 years. Age, marital status, menopausal, residential area, parda obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
42
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 18 publications
8
42
2
1
Order By: Relevance
“…This finding is slightly different from a study done in Shaukat Khanum Memorial Cancer Hospital and Research Centre Lahore, that showed vitamin D deficiency in 76.7% of controls and 95.6% of cases 4. However, there is marked difference in our findings as compared to a study of Crew et al that showed vitamin D deficiency (levels less than 20ng/ml) in 28% of controls and 33% of cases 1.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is slightly different from a study done in Shaukat Khanum Memorial Cancer Hospital and Research Centre Lahore, that showed vitamin D deficiency in 76.7% of controls and 95.6% of cases 4. However, there is marked difference in our findings as compared to a study of Crew et al that showed vitamin D deficiency (levels less than 20ng/ml) in 28% of controls and 33% of cases 1.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study 71.4% of cases and 46.2% of controls were overweight that may link increased frequency of vitamin D deficiency in cases as compared to controls because of high BMI as shown in study of Imtiaz et al4 The topic of vitamin D deficiency and breast cancer risk is a field of intense study and many aspects of it require further investigations.…”
Section: Discussionsupporting
confidence: 55%
“…Concerning low levels, this is in agreement with a previous study, which showed that lower 25OHD 3 was associated with a larger tumour size [43]. The results regarding vitamin D and tumour grade have been inconclusive in previous studies and our study showed no clear relation [44,45].…”
Section: Discussionsupporting
confidence: 94%
“…The VDR has been found in various tissues, including cardiac myocytes, b-cells in the pancreas, immune cells, and other peripheral tissues that indicate the broad role of 1,25(OH) 2 D 3 in human (Churilla et al, 2012). Reduced vitamin D status has been associated with either poor prognosis or development of lung, thyroid, breast, gastric, colon, and head and neck cancers (Cheng and Neuhouser, 2012;Imtiaz et al, 2012;Orell-Kotikangas et al, 2012;Pereira et al, 2012;Roskies et al, 2012;Ren et al, 2012). Decreased levels of vitamin D have also been found in patients with ovarian cancer as compared to the general population (Bakhru et al, 2010).…”
Section: Discussionmentioning
confidence: 99%